Evaluación de los indicadores productivos en pollos broiler con la aplicación de la esencia del eucalipto (Eucaliptus globulus) al 1 y al 3 % en el agua de bebida en el cantón Salcedo - Jiménez Gavilánez, Ángel Wilfrido (2016)
This work research was conducted in 60 Ross 500 broiler chickens of one day of born, in order to assess eucalyptus oil 1% and 3% and the corresponding control treatment separated into groups of 20 chickens, within the objectives it is to determine specific production parameters such as weight gain, feed intake, morbidity, mortality, feeding conversion and the cost benefits. The research was conducted in the Cotopaxi province, in Salcedo canton, in Antonio Jose Holguin Parish. Getting started treatment two weighing 74.9 g. concludes with 2117.5 g. with 1.92 feed conversions and a final cost to $ 3.36 for each chicken....